PERANAN PENYIDIK PEGAWAI NEGERI SIPIL BEA DAN CUKAI DI WILAYAH HUKUM KOTA DUMAI DALAM MENANGANI KASUS PENYELUNDUPAN BAWANG MERAH BERDASARKAN UNDANG UNDANG NOMOR 17 TAHUN 2006 TENTANG KEPABEANAN - Rahmat Satriawan; Evi Deliana; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
As a developing country and island countries such as Indonesia sometimes experience a disruption and obstacles to the smoothness of state revenues, due to the occurrence of a smuggling crime. It is this form of evil that impedes the course of economic development, because a lot of state money is not picked up by the crime of smuggling. In addition smuggling crime is a latent danger that threatens the country's economy as well as the survival of a country. As for the purpose of writing this thesis, namely; Firstly, to know the role of Civil Servant Investigator of Customs and Excise in handling smuggling case of onion based on Law number 17 of 2006 concerning Customs in Dumai City Law Area, Second, to know what obstacles are found by Customs Civil Servant Excise in handling the case of smuggling of shallots in the Dumai City Legal Territory.The type of research is sociological legal research is research that want to see the correlation between law and society, so as to reveal the effectiveness of law enforcement in society. The research was conducted at Dumai City Customs and Excise Inspection and Service Office, while the population and sample were the whole parties concerned with the problems studied in this study, the data source used, the primary data and the secondary data, the data collection technique in this study by interview And literature study.From the results of research problems there are three main things that need attention. First is expected to Civil Servant Investigators in realizing their role as law enforcement officers are expected to always be consistent in handling smuggling of shallots in terms of Preventive and Repressive. In the role of the Preventive role, it is more routine to conduct counseling to the community and more regularly patrols less smuggling activities such as in ports prone to access smuggling. Secondly, it is expected to Civil Servant Investigator of Customs and Excise of Dumai City in realizing its role especially in the section of investigation in carrying out its duties and obligations to always professional despite the constraints in performing the question as investigator, but it is also expected to improve its performance so that smuggling action can be minimizedKeywords: Role - Customs – Smuggling